Viral Load, Integration and Methylation of E2BS3 and 4 in Human Papilloma Virus (HPV) 16-Positive Vaginal and Vulvar Carcinomas - Lillsunde Larsson, Gabriella; Helenius, Gisela; Sorbe, Bengt; Karlsson, Mats G. (PloS one, 2014)
To investigate if viral load, integration and methylation of E2BS3 and 4 represent different ways of tumor transformation in vaginal and vulvar carcinoma and to elucidate its clinical impact. Fifty-seven samples, positive for HPV16, were selected for the study. Detection of viral load was made with realtime-PCR using copy numbers of E6 and integration was calculated from comparing E2 to E6-copies. Methylation of E2BS3 and 4 was analysed using bisulphite treatment of tumor DNA, followed by PCR and pyrosequencing. Vaginal tumors were found to have a higher viral load (p = 0.024) compared to vulvar tumors but a high copy number (> median value, 15,000) as well as high methylation (>50%) was significantly (p = 0.010 and p = 0.045) associated with a worse cancer-specific survival rate in vulvar carcinoma, but not in vaginal carcinoma. Four groups could be defined for the complete series using a Cluster Two step analysis; (1) tumors holding episomal viral DNA, viral load below 150,000 copies not highly methylated (n = 25, 46.3%); (2) tumors harboring episomal viral DNA and being highly methylated (>50%; n = 6, 11.1%); (3) tumors with viral DNA fully integrated (n = 11, 20.4%), and (4) tumors harboring episomal viral DNA and being medium- or unmethylated (<50%) and having a high viral load (> total mean value 150,000; n = 12, 22.2%). The completely integrated tumors were found to be distinct group, whilst some overlap between the groups with high methylation and high viral load was observed. HPV16- related integration, methylation in E2BS3 and 4 and viral load may represent different viral characteristics driving vaginal and vulvar carcinogenesis. HPV16- related parameters were found to be of clinical importance in the vulvar series only.